PSYCHOLOGY-BASED STUDENT MANAGEMENT: A QUALITATIVE STUDY ON STRATEGIES TO STRENGTHEN STUDENTS’ LEARNING MOTIVATION AND ACADEMIC ACHIEVEMENT - Imam Wahyono; Fitriatul Masruroh; Ahmad Aziz Fanani (International Conference on Humanity Education and Society (ICHES), 2026)
This study aims to address the main questions of how psychology-based student management is implemented at MAN 2 Banyuwangi, its role in strengthening students’ learning motivation and academic achievement, and the factors that hinder its implementation. The study is positioned within the field of educational management, emphasizing the integration of educational psychology approaches in student management practices at a public Islamic senior high school. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews with the principal, vice principal for student affairs, guidance and counseling teachers, homeroom teachers, and students, and were reinforced by observations and document analysis. The data were analyzed descriptively using the interactive analysis model proposed by Miles and Huberman. Data trustworthiness was ensured through triangulation and member checking. The findings indicate that psychology-based student management is implemented in an integrated manner through psychological assessment from the student admission process, preventive and developmental guidance and counseling services, personal mentoring by homeroom teachers, and collaboration among educational stakeholders. These strategies significantly contribute to fulfilling students’ basic psychological needs (autonomy, competence, and relatedness) which in turn enhance learning motivation and academic achievement. However, the implementation faces several challenges, including the limited number of guidance and counseling teachers, administrative workload, limited service time, and varying levels of family support.